(untitled) (Journal of Population and Development, 2024)
This paper attempts to overview the practices of human responses and adaptation strategies to natural hazards, particularly from landslides and floods. Moreover, it also aims to find out the appropriate response measures for developing countries like Nepal. This paper is prepared by the systematic reviews of related articles published in different peer-reviewed and scientific journals. Initially, the relevant papers were selected using keywords like hazards, disasters and human response to natural disasters. Then, the 64 papers were chosen and this paper was developed. There are different factors to determine the occurrence of disasters on the earth such as geology, topography, climate, topographic aspects, slope and biological activities. Processes and causes contributing to landslides can be put into three categories such as geological/morphological, physical, and human/anthropogenic causes. This study will be very helpful to entire developing countries in general and Nepal in particular as well as agencies and organizations involved in disaster risk reduction and disaster management. The impact of disasters is exacerbated by the lack of appropriate measures for mitigating their impacts. Hence, it will be the foundation for disaster risk reduction in Nepal.